Mass media utilization to promote public behavior change during COVID-19 situation: A population survey of Dhaka city - Miah, Md. Solayman; Eashat, Md. Fahim Sharker; Purba, Nafisa Habib; Jhily, Nusrat Jahan; Islam, Md Shahedul (Recent Research in Science and Technology, 2022)
A huge amount of information associated with the novel coronavirus disease 2019 (COVID-19) outbreak was circulated by mass media in Bangladesh. There has been a rare example so far of how media intervention during the epidemic can affect the public behaviour of Bangladesh. We aimed to assess mass media’s influence on changing public behaviour during the second wave of COVID-19. An online cross-sectional survey among 416 Bangladeshi respondents was conducted between August and September 2021. Besides descriptive statistics, datasets were analyzed through a set of statistical methods such as Pearson’s correlation coefficient, and stepwise multiple regression model. The results showed that knowledge level change towards COVID-19 (10 items) had the highest association with behaviour change towards COVID-19 (16 items), indicating a high adoption of public behavior change. There was a positive significant relationship between the behaviour change towards COVID-19 (16 items) with the media’s role in making awareness regarding COVID-19 (r= 0.342, p < .001), while there was a negative relationship between the behaviour change towards COVID-19 (16 items) of the respondents with age of participants (r= -.234, p < .001). The results also disclosed that knowledge level, media credibility, and media check-in had the largest contribution to influence the public behavior change. We also found that social media was highly used media as expected during the COVID-19 outbreak. The outcomes of the survey have vital implications for public behavior change and may support infectious disease suppression and control. Our outcomes also stress the significance of the reliability of information shared via mass media outlets and practical strategies to counter misinformation during the COVID-19 outbreak.